PEMBERIAN DOLOMIT DENGAN PUPUK FOSFAT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea (L.)) - Simanjuntak, Wedia; Tabrani, Gunawan; ', Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research was aimed to increase growth and yield of peanut through the provision of dolomite and phosphate fertilizer. This research was conducted at the experiment land of Agriculture Faculty University of Riau, Pekan baru from June 2014 to September 2014. This research used factorial completely randomized design (CRD) consisted of two factors and three replications. As for the treatment are: factor 1 is dolomite dose consist of three level 0,00 kg/m2,0,62 kg/m2 and 1,24 kg/m2. Factor 2 is phosphate fertilizer consist of three level 0,00 g/m2, 14,40 g/m2 and 28,80 g/m2. The results of this research showed that the combination of dolomite dose of 0,62 kg/m2 with phosphate fertilizer 28,80 g/m2 provide the best growth and yield of the plant height parameters, number of seeds/plant and dry weight of seeds/1,44 m2. The best results obtained 543,33 g/m2 (3,77 ton/ha) through combination of dolomite dose of 6,20ton/ha with phosphate dose of 0,20 ton/ha. Keywords: peanuts, dolomite, phosphate fertilizer